Comparison of Rate of Recurrence of Otitis Media with Effusion(Otorrhea) in Patients Treated by Myringotomy and Tympanostomy Tubes with Patients Treated by Additional Adenoidectomy - Nighat Arif, Muhammad Ajmal, Nausheen Qureshi (Journal of Rawalpindi Medical College, 2014)
Background: To compare the frequency of recurrence of otitis media with effusion in patients treated by myringotomy and tympanostomy tube insertion with patients treated by adenoidectomy, myringotomy and tympanostomy tubes. Methods: In this comparative study patients with otitis media with effusion, who were selected for the study were divided into two groups . Patients in group A(n=52) underwent myringotomy and tympanostomy tubes, while in group B(n=50), the patients underwent adenoidectomy, myringotomy and tympanostomy tubes.There was history of OME of atleast 03 months which did not respond to medical treatment and nasal obstruction( snoring, mouth breathing). Patients with previous history of ENT surgery and acute infection were excluded. Myringotomy was done by giving radial or circumferential incision about 2 to 3 ml in tympanic membrane under microscope. Shepard’s ventilation tube was used as grommet in all cases. Patients were scheduled for follow up at 01, 02, and 06 months postoperatively to assess the otorrhea. The diagnosis of otorrhea was based on otoscopic visualization of discharge exuding through the tube lumen after gently cleaning the external auditory canal. Episodes of otorrhea were treated with oral antimicrobial drugs and if persistent then with ototopical medication. Final outcome of the study were documented at 06 months Results: Mean age of patients was 3.2 + 1.1 and 2.9 + 1.2 years in group A and B, respectively. Mean duration of illness was 3.8 + 1.2 and 4.1 + 1.1 months in group A and B respectively. Recurrence of disease was more commonly present in male patients, patients with greater duration of illness and in group A patients. There was significant difference in recurrence rate of the disease in both groups ( p-value= 0.0029<0.05). Age stratification indicates that the rate of recurrence dropped with advancing age in both groups. Gender stratification showed that recurrence of the disease is more commonly present in male patients in both groups. Recurrence rate was higher in patients with greater duration of illness in both groups. Conclusion: There was statistically significant difference( p-value= 0.0029<0.05) in the rate of recurrence of otitis media with effusion (otorrhea) among the two groups with fewer cases of recurrence in group B who underwent adenoidectomy, myringotomy and tympanostomy tubes.